2022
DOI: 10.1101/2022.10.04.510836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Imaging Reveals Diverse Functions of Tricarboxylic Acid Metabolites in Root Growth and Development

Abstract: Understanding how plants grow is critical for agriculture and fundamental for illuminating principles of multicellular development. Here, we apply chemical mapping of the developing maize root using desorption electrospray ionization mass spectrometry imaging (DESI-MSI). This technique reveals a range of small molecule distribution patterns across the gradient of stem cell differentiation in the root. To understand the developmental logic of these patterns, we examined tricarboxylic acid (TCA) cycle metabolite… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, the redox state appears to modulate and balance S-RNase condensation or diffusion ability to ensure its optimal activity in self-incompatible pollen tubes, which is similar to the reversible formation of condensates by the Pbp1 LC domain, making the protein adapt cells to mitochondrial activity by H 2 O 2 -mediated oxidation (Kato et al, 2019). The H 2 O 2 levels in certain concentration ranges can promote root growth (Zhang et al, 2023) similar to our results, suggesting increasing H 2 O 2 contents promote growth under anaerobic or hypoxic survival conditions. This finding indicates that we can regulate the SRC formation in a switch-like pattern by altering the redox state to realize reversible conversion of self-pollen incompatibility and CPC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the redox state appears to modulate and balance S-RNase condensation or diffusion ability to ensure its optimal activity in self-incompatible pollen tubes, which is similar to the reversible formation of condensates by the Pbp1 LC domain, making the protein adapt cells to mitochondrial activity by H 2 O 2 -mediated oxidation (Kato et al, 2019). The H 2 O 2 levels in certain concentration ranges can promote root growth (Zhang et al, 2023) similar to our results, suggesting increasing H 2 O 2 contents promote growth under anaerobic or hypoxic survival conditions. This finding indicates that we can regulate the SRC formation in a switch-like pattern by altering the redox state to realize reversible conversion of self-pollen incompatibility and CPC.…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids have important roles in plant physiology as central intermediates in carbon metabolism, pH regulation, and redox regulation ( Igamberdiev and Eprintsev, 2016 ), with many types having been spatially mapped in situ . For example, DESI-MSI of maize roots in longitudinal sections showed that tricarboxylic acid (TCA) cycle intermediates were enriched in developmentally distinct regions, with implications for plant growth and development ( T. Zhang et al , 2023 ). While succinate was enriched in the meristem, three TCA intermediates, aconitate, fumarate, and malate, were enriched in the differentiation zone.…”
Section: Expanding the Spatial Metabolome Coveragementioning
confidence: 99%
“…Chemical data containing mass spectra at each tissue spot are then processed using specialized software to identify compounds, quantify their abundance, and generate spatial images. Five representative MSI studies are highlighted to illustrate spatial heterogeneity of metabolites: (top left) lipids in Arabidopsis thaliana seeds (graphical abstract, reprinted from Sturtevant et al , 2017 with permission from Elsevier), (bottom left) sugars, organic acids, and lipids in maize roots (modified from T. Zhang et al , 2023 ), (middle top) alkaloids in periwinkle petals [reproduced from Dutkiewicz et al (2021) , with permission], (middle bottom) vitamins in engineered tomato fruit (modified from Li et al , 2022 ), (right) lipid marker and Δ9-THCA in cannabis sugar leaves [reproduced from Lorensen et al (2023b) , with permission]. Additional details are described within the text and in corresponding articles.…”
Section: Introduction Mass Spectrometry Imaging: a Brief Ove...mentioning
confidence: 99%
“…More large‐scale metabolite profiling indicates marked changes in several TCA cycle metabolites as cells transition from making primary walls to secondary cell walls (Li et al., 2016). More recently, the group of Alexandra Dickenson revealed via mass spectral imaging that intermediates of the TCA cycle appear to envoke distinctive developmental transitions which are independent of ATP levels (Zhang et al., 2023). A more direct link to cellulose synthesis is provided by sucrolytic activities.…”
Section: Metabolic Regulation Of Cellular Programsmentioning
confidence: 99%